Research progress on the induction of immunogenic cell death in tumor immunotherapy using a sonodynamic therapy nanoparticle delivery system - Du, Yang; Yang, Jiangnan; Xu, An; Chen, Shuai; Fu, Deyuan (Frontiers in Immunology, 2025)
ICD is critical for enhancing antitumor immune responses in tumor immunotherapy. SDT employs ultrasound to activate Sonosensitizers, generating ROS that induce cytotoxic tumor cell death and trigger ICD through the release of DAMPs. However, standalone SDT faces challenges such as limited Sonosensitizers accumulation and poor tissue specificity. Nanoparticle-mediated SDT addresses these limitations by improving Sonosensitizers delivery, tumor targeting, and biocompatibility. This review explores how nanotechnology enhances SDT to induce ICD, focusing on its integration with chemotherapy and immunotherapy to achieve synergistic antitumor effects. We highlight recent advancements in multifunctional nanoplatforms that optimize ROS production, reprogram the tumor microenvironment, and enhance immune activation. By overcoming the constraints of conventional therapies, nanoparticle-mediated SDT offers a promising strategy for precise, effective, and low-toxicity tumor immunotherapy, with potential for clinical translation.